Estudio de clima laboral e implementación de planes de mejora para la dirección técnica de finanzas y presupuestos de la Universidad Politécnica Salesiana, sede Quito. - López Mancero, Yadira Estefanía (2015)
In ancient times, organizations with the purpose of fulfilling its mission were focused priority in the production of goods and services rather than the welfare of workers, which caused problems with the administration, tasks and staff; for this reason, this type of administration changed during the years, paying greater attention to the needs of the employees, to whom need to develop in a healthy working environment, that gives them confidence and trust in business and personal aspects, that influence the level of satisfaction. When someone refers to their place of work, usually refers to the working environment perceived in the organization, hence the importance of a measurement project to help establish improvement plans to the Technical Department of Finance and Budgets UPS. The methodology used for the measurement is as follows: Quantitative methodology  CLA (Employee Satisfaction Questionnaire) Consisting of two axes are: business person, each axis contains four factors, the first covers organization, innovation, information, conditions, while the second provides for involvement, self, relationships and address. Qualitative methodology  Individual interviews: Helps to know the perception of employees regarding the various factors of CLA.  Group interview: Refers an overview of the group in relation to the factors addressed by the CLA. After analyzing the data obtained from the applied tools, improvement strategies where explored according to each of the factors working environment questionnaire, giving emphasis to the suggestions made by the members area.